98.6k views
4 votes
Please help explanation if possible

Please help explanation if possible-example-1
User Overclover
by
5.6k points

1 Answer

2 votes

Answer:

(- 3, 2 )

Explanation:

Given the 2 equations

x + 3y = 3 → (1)

- 2x + 3y = 12 → (2)

Subtract (1 ) from (2) term by term to eliminate y

- 2x - x + (3y - 3y) = 12 - 3

- 3x = 9 ( divide both sides by - 3 )

x = - 3

Substitute x = - 3 into either of the 2 equations and solve for y

Substituting into (1)

- 3 + 3y = 3 ( add 3 to both sides )

3y = 6 ( divide both sides by 3 )

y = 2

solution is (- 3, 2 )

User Arnauld
by
5.5k points